The energy transition in Asia: Country priorities, fuel types, and energy decisions - Etienne Romsom; Kathryn McPhail (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper provides an overview of the energy transition in Asia. It sets out the underlying drivers and how these set energy transition priorities in China, India, and South East Asia. It particularly describes the role of (liquefied) natural gas in the growing energy demand and changing energy mix. A comparison is then made for each of the three regions on how four main fuel types (coal, oil, natural gas, and renewables) contribute differently to eight energy transition priorities. An analytical model is developed that links a ranking of energy transition priorities to an alignment with the four fuel types. The model determines which fuel types are most aligned with a certain set of energy transition priorities. The predicted alignment with fuel types appear to match the energy investment decisions well for China, India, and South East Asia.
Keywords: Q2; Q4; 330; renewable resources; energy; energy utilities; fuel; gas